PELESTARIAN RUMAH PANGGUNG (RUMAH TRADISIONAL BERBAHAN DASAR KAYU) DI DESA PENANGGUNGAN, TANGGAMUS - Leni Susanti; Indra Gumay Febryano; Yulia Rahma Fitriana; Rudi Hilmanto (Forestry Study Program University Of Mataram, 2022)
The traditional wooden house has become a symbol for the indigenous people of Lampung. The research objective is to explain the factors that influence the community to maintain its traditional wooden houses. This research used the qualitative approach within a case study method in Penanggungan Village, Tanggamus District, Lampung Province. By collecting data through in-depth interviews, involved observations, and documentation studies, then analyzed some factors that influence the community to maintain the stilt house. The results showed that the local community held its wooden-based stage due to various factors, especially: cultural, heritage, raw materials, community economic conditions, public knowledge, and government policies. The government needs to make local regulations to maintain the existence of the remaining stilt houses and provide subsidies to the community to maintain its sustainability. In addition, the cultivation of the types of wood that used and its types substitution needs to be encouraged to avoid the scarcity of raw materials for stilt houses.